Clinical case of stenting of the left main coronary artery under artificial circulation: a case report - Jazver, Jibran Mohamed; Panishkumar, Patel Krushikumar; Samarakoon, Isuri Umayangana; Logus, Gardhi Hettiarachchige Nisal Gawesha; Kalatsei, Liudmila; Cherniak, Alexander (International Journal of Research in Medical Sciences, 2024)
This case report documents the intricate management of a 61-year-old patient presenting with acute coronary syndrome, permanent atrial fibrillation (AF), and a history of prior cardiac interventions. Coronary angiography revealed significant left coronary artery pathology, necessitating intervention under artificial circulation. Percutaneous coronary intervention was deemed unsuitable due to high risk, prompting the installation of an intra-aortic balloon counter pulsation system. Subsequent interventional stenting of the left main coronary artery (LCA) was successfully performed. Despite post-operative complications, including pneumonia and renal dysfunction, the patient exhibited steady improvement, highlighting the importance of tailored, multidisciplinary care in complex cardiovascular cases.